2021
DOI: 10.7717/peerj.11233
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a ferroptosis-related gene signature (FRGS) for predicting clinical outcome in lung adenocarcinoma

Abstract: Background Lung adenocarcinoma (LUAD) is the most common pathological subtype of lung cancer. Ferroptosis, an oxidative, iron-dependent form of necrotic cell death, is highly associated with tumorigenesis and cancer progression. However, the prognostic value of ferroptosis progress in LUAD was still rarely be investigated. Methods Herein, we collected three mRNA expression profiles and 85 ferroptosis-related genes from public databases. The “limma” package was used to identify ferroptosis-related differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…A previous study showed that repression of aldehyde dehydrogenase 2 family (ALDH2) promotes lung tumor progression through accumulated acetaldehyde and DNA damage (Li et al, 2019). CYBB, a gene related to ETC and ferroptosis, associated signature could predict the 1-, 3-, and 5-year survival rates of LUAD patients (Wang et al, 2021). Also, mutation of the CYBB gene selectively affects macrophages and is associated with immune changes (Bustamante et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that repression of aldehyde dehydrogenase 2 family (ALDH2) promotes lung tumor progression through accumulated acetaldehyde and DNA damage (Li et al, 2019). CYBB, a gene related to ETC and ferroptosis, associated signature could predict the 1-, 3-, and 5-year survival rates of LUAD patients (Wang et al, 2021). Also, mutation of the CYBB gene selectively affects macrophages and is associated with immune changes (Bustamante et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…FANCD2, a nuclear protein that responds to DNA damage repair, negatively regulated ferroptosis of bone marrow injury in cancer treatment and could be a potential target of anticancer therapies ( Song et al, 2016 ). In addition, a 10 ferroptosis-related genes signature and a ferroptosis-related gene signature with five genes were constructed to predict the prognosis of patients with LUAD ( Wang S. et al, 2021 ; Zhu et al, 2021 ). In general, ferroptosis-related genes play important roles in the progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential for regulating iron and ROS homeostasis in cells and plays a key role in promoting cancer cell proliferation and supporting tumor growth and metastasis [38]. Additionally, CISD1 is overexpressed in both lung adenocarcinoma and breast cancer [39,40].…”
Section: Discussionmentioning
confidence: 99%